2021
DOI: 10.1080/19490976.2021.1900997
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics reduce self-reported symptoms of upper respiratory tract infection in overweight and obese adults: should we be considering probiotics during viral pandemics?

Abstract: Gut microbiome manipulation to alter the gut-lung axis may potentially protect humans against respiratory infections, and clinical trials of probiotics show promise in this regard in healthy adults and children. However, comparable studies are lacking in overweight/obese people, who have increased risks in particular of viral upper respiratory tract infections (URTI). This Addendum further analyses our recent placebo-controlled trial of probiotics in overweight/obese people (focused init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…The main basis for this possibility is that several clinical studies have reported alterations of gut microbiota/dysbiosis of COVID-19 patients [89][90][91], and it is well-known that probiotics are efficient in positively modulating the gut microbiome in many cases of dysbiosis as has been noted in systematic reviews and meta-analyses [92][93][94][95]. To date, one clinical study has addressed this question, and it concluded that support for further trials to assess the potential role of probiotics in preventing viral URTI (and possibly also COVID-19) is warranted [96].…”
Section: Discussionmentioning
confidence: 99%
“…The main basis for this possibility is that several clinical studies have reported alterations of gut microbiota/dysbiosis of COVID-19 patients [89][90][91], and it is well-known that probiotics are efficient in positively modulating the gut microbiome in many cases of dysbiosis as has been noted in systematic reviews and meta-analyses [92][93][94][95]. To date, one clinical study has addressed this question, and it concluded that support for further trials to assess the potential role of probiotics in preventing viral URTI (and possibly also COVID-19) is warranted [96].…”
Section: Discussionmentioning
confidence: 99%
“…Weaning piglets are susceptible to diarrhea caused by pathogenic E.coli (e.g., ETEC) infection. Growing studies indicate that probiotics prevent pathogenic bacteria colonization and proliferation ( 12 , 13 ). Manuela et al ( 24 ) showed that probiotics inhibited pathogenic bacteria by producing antimicrobial metabolites and competing for energy substances.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great opportunity to develop new strategies for preventing intestinal pathogen infection in weaning piglets. Probiotics can prevent infections caused by pathogens such as Clostridium difficile ( 12 , 13 ). However, the ability of probiotics to prevent infection varies ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of probiotics have been explained with improving barrier function and immunity through the actions of cell components and metabolites of probiotics [ 38 , 39 ]. There are direct effects, including microorganism-associated molecular patterns (MAMPs) and pattern recognition receptors (PRRs), in the gut mucosa [ 40 ].…”
Section: Effects Of Probiotics and Synbiotics During Critical Illnessmentioning
confidence: 99%
“…In gut microbiota of COVID-19 patients, the decrease in normal gut microbiota bacteria, such as Eubacterium ventricosum , Faecalibacterium prausnitzii , Reseburia , and Lachnospiraceae, and the increase of opportunistic bacteria, such as C. hathewayi , Actinomyces viscosus , and B. nordii , was observed [ 64 ]. Probiotics/synbiotics are one of the promising therapies for COVID-19 to maintain gut microbiota and prevent the exacerbation of pneumonia [ 39 ]. In 200 adults with severe COVID-19 pneumonia, patients treated with several kinds of probiotics were associated with a reduced risk for death [ 65 ].…”
Section: Effects Of Probiotics and Synbiotics During Critical Illnessmentioning
confidence: 99%